Hacia la creación de un mecanismo para hacer más viable la figura de la extensión de jurisprudencia a terceros (2020)
The present text presents the analysis of the jurisdiction extension to third parties (FEJT in Spanish) of the Consejo de Estado in light of the 1991 Colombia Constitution and the dispositions of the CPACA and the CGP to determine if it has been efficient in the administrative seat and if it has contributed to the decongestion of the judiciary. For that, the precedents of the FEJT, as well as Spain and Costa Rica?s case-laws, were examined. Next, its incorporation in the Colombian legal system is studied: its aims and its functioning in the administrative and judicial seats. An analysis of data provided by several public entities was carried out to determine the jurisprudence?s efficacy, operativity, and efficiency...